Character Analysis of Characters in the Compass 2020 Short Story Collection Tiger : Analisis Karakter Tokoh dalam Kumpulan Cerpen Macan Pilihan Kompas 2020 - Radila Agustina; Suhardi; Dody Irawan; Ahada Wahyusari; Abdul Malik; Tessa Dwi Leoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to describe the characters of the charaters in the short story collection Tiger Compass 2020 by using a psychological dimension approach. This type of research is qualitative, this research method is descriptive using an objective approach. The data collection techniques used are reading and recording. The data analysis technique used is content analysis technique. The results of this study obtained a variety of character traits using psychic or psychological charater dimensions. The characters in the short story collection are, (1) kindness, (2) brave, (3) philanthrope, (4) empathy, (5) honesty, (6) cruelty, (7) independent, (8) responsibility, (9) patience, (10) politeness.